Local in-plane strength and stiffness of stud-to-sheathing fastener connections in LSF wall panels. (March 2021) - Abeysiriwardena, Tharindu; Peiris, Mithum; Mahendran, Mahen
Abstract: Light-gauge steel framed (LSF) wall systems of low- and mid-rise buildings are made of cold-formed steel studs and tracks and lined with sheathing material such as gypsum plasterboard. The stiffness provided by sheathing can be idealised into three main components, namely, in-plane, out-of-plane and rotational stiffness. Idealised in-plane stiffness has been used commonly in the numerical and analytical studies of cold-formed steel stud walls. Experimental evidence shows that local in-plane response depends on several factors such as stud thickness, thickness of sheathing material, screw fastener diameter, fastener end and edge distances, number of layers of sheathing material and environmental conditions, of which the effects of most of them are not well understood. An experimental study was therefore conducted to investigate the non-linear local in-plane strength and stiffness of screw-fastened stud-to-gypsum plasterboard sheathing connections by varying a range of parameters affecting their stiffness and capacities. The resulting load-displacement curves were analysed, and models of characteristic curves were developed. A finite element model and an analytical model were then developed to determine the local in-plane response and initial stiffness of stud-to-sheathing screw fastener connections, by employing pure bearing response of sheathing, and were validated using experimental results. Highlights: Experimentally investigated non-linear local in-plane behaviour of stud-to-gypsum plasterboard screw connections. Identified local in-plane stiffness as a sum of stud-to-fastener connection stiffness and sheathing bearing stiffness. Experimentally investigated pure bearing response of gypsum plasterboards of varying thicknesses. Developed a simple finite element model by using the bearing response of gypsum plasterboards and validated. Developed an analytical model to calculate initial local in-plane stiffness of stud-to-sheathing connections and validated.